2006
DOI: 10.1111/j.1600-6143.2006.01516.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor Lymphoid Organs Are a Major Site of Alloreactive T-Cell Priming Following Intestinal Transplantation

Abstract: We hypothesized that lymphoid organs within intestinal allografts contribute to their immunogenicity. Consistent with this hypothesis recipient T cells rapidly migrated to the lymph nodes and Peyer's patches of syngeneic and allogeneic intestinal grafts such that at 24 h approximately 50% of the lymphocytes isolated from donor lymphoid organs were of recipient origin. However, only in the lymphoid organs of allografts did recipient T cells display an activated phenotype, proliferate and produce IFNc . Rejectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Both clinical and experimental data have demonstrated that intestinal allografts elicit a strong immune response (24). The severity of this immune response contributes to the lowered graft and patient survival rates in patients undergoing SBTx, especially when compared with other organs such as the heart or kidney (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Both clinical and experimental data have demonstrated that intestinal allografts elicit a strong immune response (24). The severity of this immune response contributes to the lowered graft and patient survival rates in patients undergoing SBTx, especially when compared with other organs such as the heart or kidney (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Mandy Ford and Kenneth Newell, Emory University). Mice were genotyped for the wild-type and aly mutant alleles of Map3k14 (mitogen-activated protein kinase kinase kinase 14) gene by running two separate PCRs with allele-specific forward primers [5′-CACATCCCGAGCTACTTCAACA-3′ for aly and 5′-CACATCCCGAGCTACTTCAACG-3′ for wild-type NF-κB-inducing kinase (NIK)] and a common reverse primer (5′-CCTTCGGGGACTCTACAGGC-3′ for NIK) (50). The mutant and wild-type NIK alleles both yielded 266-bp PCR products.…”
Section: Methodsmentioning
confidence: 99%
“…However, little is known about how HvG and GvH responses influence the turnover, phenotype and repertoire of tissue-resident T-cell populations following transplantation. Studies in mice( 10 ) and humans( 11 ) have indicated that recipient-derived T cells repopulate the GALT (Gut-Associated Lymphoid Tissues) of intestinal allografts early after transplantation. However, the turnover rate of mucosal T cells after intestinal transplantation has been investigated in only a few patients( 12 ) in cross-sectional studies( 11 ), without phenotype or repertoire analysis( 11, 12 ).…”
Section: Introductionmentioning
confidence: 99%